Hydrogen Storage Materials
The pore-containing carbon nitride tubes prepared through hydrothermal treatment and calcination solve the limitations of existing solid hydrogen storage materials in hydrogen storage performance and safety, and achieve efficient hydrogen absorption and storage, which is suitable for transportable fuel cells.
Patent Information
- Application Number
- CN202080038567.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-05
- Filing Date
- 2020-07-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-07-02
AI Technical Summary
Existing solid hydrogen storage materials have limitations in hydrogen storage performance, safety and weight density, especially under high pressure conditions, which makes it difficult to meet the needs of transportable fuel cells.
By hydrothermal treatment of melamine and calcining in a sealed container, porous carbon nitride tubes with porous structures were prepared as solid hydrogen storage material, utilizing its high surface area and excellent hydrogen absorption properties.
Efficient hydrogen absorption and storage is achieved, providing a safer and lighter solid hydrogen storage solution suitable for transportable fuel cell systems.
Smart Images

Figure BDA0003371686060000121 
Figure BDA0003371686060000151 
Figure BDA0003371686060000161
Abstract
Description
Technical Field
[0001] The present invention relates to hydrogen storage, and in particular to a solid-state hydrogen storage material and a method for preparing the solid-state hydrogen storage material. Background Art
[0002] Hydrogen is an attractive energy carrier (i.e., fuel source) for many reasons. For example, hydrogen has a high gravimetric energy density and can be used in processes such as combustion or in devices such as fuel cells to provide power or electricity, respectively, without forming carbon dioxide.
[0003] However, many consider the storage of hydrogen to be a bottleneck in achieving a hydrogen economy. Currently, hydrogen is typically stored in high-pressure tanks (e.g., ~700 bar) for use in transportable fuel cells (e.g., in electric vehicles). Tanks that are strong enough to withstand such high pressures are typically heavy, which offsets the high gravimetric energy density of hydrogen. High pressures also raise safety issues. These limitations are amplified in gas stations, which typically store larger quantities of hydrogen at higher pressures.
[0004] Solid-state hydrogen storage systems have been used to address some of these limitations. However, solid-state hydrogen storage systems still have some limitations. For example, lithium and magnesium-based alloys have high hydrogen storage capacities, but the temperatures at which hydrogen is released are too high to be used in vehicle-mounted systems (e.g., for transportable fuel cells). AB5-type alloys have moderate hydrogen storage properties, are easy to initially activate, have low platform pressures, and have low ambient operating temperatures, but the hydrogen capacity is generally too low (~1.4wt%) to be used in transportable fuel cells. Chemical hydride systems have very high gravimetric hydrogen capacities, but effective rehydride methods remain challenging. Metal-organic frameworks generally require very low hydrogenation temperatures and / or exhibit slow dehydrogenation rates.
[0005] There is a need for alternative materials suitable for use as solid-state hydrogen storage materials. There is also a need for materials suitable for use as transportable solid-state hydrogen storage materials. Summary of the invention
[0006] In a first aspect, the present invention provides a method for preparing a porous carbon nitride tube, the method comprising:
[0007] (a) hydrothermally treating melamine by subjecting the melamine in contact with water to a temperature of about 100° C. to about 300° C.; and
[0008] (b) calcining the hydrothermally treated melamine at a temperature of about 500° C. to about 600° C. in a sealed container.
[0009] Advantageously, the porous carbon nitride (CN) tubes prepared by the method of the present invention can have the properties required for hydrogen storage. For example, in at least some embodiments, the porous carbon nitride tubes prepared by the method are porous and / or have a large surface area. In addition, melamine is generally readily available and inexpensive. In addition, the method of the present invention does not require foreign and / or expensive catalysts that are currently commonly used to prepare carbon nitride materials.
[0010] In some embodiments, the hydrothermally treated melamine is contacted with a filler during at least a portion of the calcination step (step (b)). In some embodiments, the filler is ceramic Al2O3 particles (eg, ceramic Al2O3 balls).
[0011] In some embodiments, the temperature in step (a) is from about 180°C to about 220°C.
[0012] In some embodiments, the temperature in step (b) is from about 540°C to about 580°C.
[0013] In some embodiments, the pores of the carbon nitride tubes have a diameter of about 1 nm to about 15 nm, specifically about 5 nm to about 7 nm.
[0014] In some embodiments, the tube has a diameter of about 0.5 μm to about 20 μm. In some embodiments, the tube has a length of about 15 μm to about 150 μm.
[0015] In a second aspect, the present invention provides a pore-containing carbon nitride tube obtained by the method according to the first aspect.
[0016] In a third aspect, the present invention provides the use of porous carbon nitride tubes obtained by the method according to the first aspect in the absorption, adsorption or desorption of hydrogen. In another aspect, the present invention provides the use of porous carbon nitride tubes obtained by the method according to the first aspect in the absorption, adsorption or desorption of gas. In some embodiments, the gas is CO2, CH4, N2O, SO2, O3, H2O, fluorinated gas, biofuel gas, synthesis gas or a mixture thereof. In some embodiments, the porous carbon nitride tubes are used as absorbents to remove gases from gas-containing atmospheres, such as removing CO2 from a container or removing greenhouse gases such as CO2, CH4, N2O, SO2, O3, H2O and fluorinated gases from production waste gas or the earth's atmosphere.
[0017] In a fourth aspect, the present invention provides a solid-state hydrogen storage material comprising a pore-containing carbon nitride tube obtained by the method according to the first aspect.
[0018] In another aspect, the present invention provides a method for preparing porous carbon nitride tubes similar to the first aspect, wherein a melamine precursor such as cyanamide or dicyandiamide is used instead of melamine. It is understood that the melamine precursor forms melamine in situ under the conditions of the hydrothermal treatment step. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Specific embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings, in which:
[0020] Figure 1 Shown are scanning electron microscope (SEM) images of (a) pure melamine and (br) melamine hydrothermally treated under different synthesis conditions, as described in the Examples.
[0021] Figure 2 Shown are SEM images of melamine cyanurate hydrothermally treated with an autoclave having (a) a volume of 100 mL, (b) a volume reduced from 100 mL to 70 mL, and (c) a volume of 100 mL but placed horizontally in an oven, as described in the Examples.
[0022] Figure 3 Shown are X-ray diffraction (XRD) patterns of (a) pure melamine and (br) hydrothermally treated melamine, as described in the Examples.
[0023] Figure 4 Shown are Fourier transform infrared (FT-IR) spectra of pure melamine and hydrothermally treated melamine, as described in the Examples.
[0024] Figure 5 Shown are SEM images (a) to (k) of CN materials prepared under different pyrolysis conditions corresponding to Table 5, as described in the Examples.
[0025] Figure 6 SEM images of selected CN materials are shown: (a) bulk g-CN; (b) H 200 -C 560 -CN; (c)H 205 -C 560 -CN;(d)H 205 -C 600 -CN, as described in the Examples.
[0026] Figure 7 Shows H 205 -C 560 Transmission electron microscopy (TEM) images of -CN: (a) microtubes; (b) nanotubes, as described in the examples. The outer diameter of the nanotubes is about 200 nm, and the thickness of the tube wall is about 30 nm. In addition to the individual nanotubes ( Figure 7b), nanotubes can also be observed along the inner wall of the microtubules ( Figure 7 a).
[0027] Figure 8 Energy dispersive X-ray spectroscopy (EDS) images of selected CN materials are shown: (a) bulk g-CN; (b) H 200 -C 560 -CN; (c)H 205 -C 560 -CN;(d)H 205 -C 600 -CN, as described in the Examples.
[0028] Fig. 9 Nitrogen adsorption-desorption isotherms at 77 K are shown for selected CN materials, as described in the Examples.
[0029] Fig.10 Shown are the pore size distributions of selected CN materials, as described in the Examples.
[0030] Fig.11 The XRD patterns of selected CN materials are shown: (a) bulk g-CN; (b) H 200 -C 560 -CN; (c)H 205 -C 560 -CN;(d)H 205 -C 600 -CN, as described in the Examples.
[0031] Fig.12 FT-IR of selected CN materials is shown: (a) bulk g-CN; (b) H 200 -C 560 -CN; (c)H 205 -C 560 -CN;(d)H 205 -C 600 -CN, as described in the Examples.
[0032] Fig.13 The pressure-composition-isotherms of the hydrogen absorption capacity of selected CN materials at 20°C are shown, as described in the Examples.
[0033] Fig.14 The correlation between surface area and H2 uptake for selected CN materials is shown, as described in the Examples.
[0034] Fig.15 Shows H 205 -C 560 - Pressure-composition-isotherms of CN at 20°C, 50°C and 100°C, as described in the Examples.
[0035] Fig.16 Shows H 205 -C 560 - Chemical adsorption measurements of CN from 20°C to 500°C, where the samples were pre-filled with 10% H2+Ar gas at 20°C, 50°C and 100°C, as described in the Examples.
[0036] Fig.17 Shows H 205 -C 560 The absorption and desorption kinetics of -CN are as described in the Examples.
[0037] Fig.18 shows that H up to 10 MPa 205 -C 560 The hydrogen storage capacity of -CN was extrapolated as described in the Examples.
[0038] Fig.19 is a schematic diagram depicting an inverted crucible (4) placed on a reaction vessel (3) containing hydrothermally treated melamine (1) and filler (2), which is sealed to a base plate (6) by a sealant (5), as described in the example of paragraph . DETAILED DESCRIPTION
[0039] In a first aspect, the present invention provides a method for preparing a porous carbon nitride tube, the method comprising:
[0040] (a) hydrothermally treating melamine by subjecting the melamine in contact with water to a temperature of about 100° C. to about 300° C.; and
[0041] (b) calcining the hydrothermally treated melamine at a temperature of about 500° C. to about 600° C. in a sealed container.
[0042] Carbon nitride is a nitrogen-rich carbonaceous material comprising carbon and nitrogen. The method of the present invention can be used to prepare porous carbon nitride tubes. In some embodiments, the method of the present invention produces porous carbon nitride tubes with a high nitrogen content. It is believed that the hydrogen storage performance increases with the increase of nitrogen content. It is believed that as more carbon atoms are replaced by nitrogen atoms, the hydrogen storage performance is improved (compared to pure carbon tubes) because the tube wall has more defects caused by nitrogen substitution. That is, the porous carbon nitride tube absorbs hydrogen, and the hydrogen absorption amount is generally improved at a higher nitrogen content. The term "C3N4" is used in the art to describe carbon nitride having a carbon-nitrogen ratio of about 3:4. As will be understood by those skilled in the art, "C3N4" can be used to describe carbon nitride having a C:N ratio similar to 3:4 but not completely 3:4 (e.g., from about 3:3.5 to about 3:4.5). As used herein, unless otherwise required by the context due to explicit language or necessary implication, the term "CN" is used to refer to carbon nitride having a carbon-nitrogen ratio close to 3:4, and may include carbon nitride having a carbon-nitrogen ratio of about 3:3.5 to about 3:4.5. The C:N ratio of the porous carbon nitride tube (sometimes referred to herein simply as a "CN tube") obtained by the method of the present invention may vary and may depend on, for example, the properties of the starting material and the conditions used in the method. The CN tube obtained by the method of the present invention generally has a C:N ratio greater than 3:2.4 (e.g., about 3:2.4 to about 3:4 or about 3:2.4 to about 3:3.86). In some embodiments, the porous carbon nitride tube has a carbon-nitrogen ratio (C:N) of about 3:2 to about 3:4, for example, about 3:2.5 to about 3:4, about 3:3 to about 3:4, about 3:3.5 to about 3:4, or about 3:3.7 to about 3:4. In some embodiments, the method of the present invention produces a porous carbon nitride tube having a carbon-nitrogen ratio of about 3:4. In some embodiments, the carbon nitride tubes obtained by the methods of the present invention may be described as "C3N4" tubes.
[0043] The method of the present invention forms carbon nitride in the form of porous tubes. As used herein, "tube" refers to an elongated structure having an outer wall surrounding an internal space, which may or may not be empty. The ends of the elongated structure may be open or closed (i.e., the tube may be open at one or both ends, or may be closed at one or both ends). The shape of the tube is not limited to cylindrical; these tubes may have a cross-sectional geometry other than circular (e.g., a regular shape, such as a square, pentagon, hexagon, etc., or an irregular shape). However, generally, the tube produced by the method of the present invention is approximately cylindrical and is generally hollow. The method of the present invention may also form other forms of carbon nitride, however, the porous carbon nitride tube is the most significant of the carbon nitride forms produced by the method, because it is believed that it is the porous carbon nitride tube that makes the material generated by the method have superior hydrogen storage properties.
[0044] The porous carbon nitride tube produced by the method of the present invention is not particularly limited by size. The porous carbon nitride tube produced by the method of the present invention generally has an outer diameter of about 1nm to about 1mm, more generally about 0.1μm to about 20μm or about 0.2μm to about 20μm (sometimes referred to herein as "diameter") and about 1μm to about 300μm, more generally about 10μm to about 200μm in length. The thickness of the tube wall is generally about 5nm to about 100nm. In some embodiments, the tube is a microtube. The microtube has a micrometer-scale diameter (i.e., an outer diameter of about 1μm to about 1000μm). In some embodiments, the tube is a nanotube. The nanotube has a nanometer-scale diameter (i.e., an outer diameter of about 1nm to about 100nm). In some embodiments, the outer diameter of the tube is about 1nm to about 1mm, for example, about 10nm to about 100μm, about 10nm to about 10μm, about 10nm to about 1μm, about 100nm to about 500nm or about 100nm to about 300nm. In some embodiments, tubes with smaller outer diameters may be preferred (e.g., from about 0.1 μm to about 20 μm or from about 0.2 μm to about 5 μm) because it is believed that better performance, such as hydrogen storage, can be obtained, which may be due to the larger surface area to weight ratio of the material. In some embodiments, the length of the tube is from about 1 μm to about 300 μm, such as from about 5 μm to about 200 μm, from about 10 μm to about 100 μm, from about 20 μm to about 80 μm, or from about 30 μm to about 70 μm. In some embodiments, tubes with shorter lengths may be preferred because it is believed that better performance, such as hydrogen storage, can be obtained, which may be due to lower energy barriers to absorption, adsorption and / or desorption of hydrogen. In some embodiments, the thickness of the tube wall is from about 5 nm to about 100 nm, such as from about 5 nm to about 70 nm, from about 10 nm to about 50 nm, or from about 20 nm to about 40 nm.
[0045] The present invention provides a method for preparing a porous carbon nitride tube (i.e., a carbon nitride tube containing holes). As used herein, "holes" refer to holes located in the tube wall (i.e., not the "ends" of the tube). Without wishing to be bound by theory, it is believed that the presence of holes increases the ability of the tube to absorb hydrogen by increasing the surface area of the carbon nitride tube material. In some embodiments, the diameter of the hole is about 1 nm to about 50 nm, for example, about 1 nm to about 30 nm, about 1 nm to about 15 nm, about 2 nm to about 10 nm, about 3 nm to about 7 nm, or about 5 nm to about 7 nm. It should be understood that the hole can be circular or irregular in shape. For irregularly shaped holes, "diameter" refers to the diameter of a circular hole having an area approximately the same as the cross-sectional area of the irregularly shaped hole. In some embodiments, the hole area accounts for about 10% to about 60% of the surface of the carbon nitride tube, preferably about 20% to about 50%.
[0046] As used herein, "hydrothermal treatment" (and variations thereof, such as "hydrothermal treatment") refers to a process in which melamine is heated in the presence of water. Hydrothermal treatment of melamine yields hydrothermally treated melamine. Hydrothermally treated melamine is considered to be melamine cyanurate, or at least predominantly melamine cyanurate.
[0047] In the method of the present invention, the hydrothermal treatment is carried out at a temperature of about 100°C to about 300°C. In other words, melamine is contacted with water and heated to a temperature of about 100°C to about 300°C. As long as melamine and water are contacted at a temperature of about 100°C to about 300°C, melamine can be contacted with water by adding water to melamine or by adding melamine to water. In some embodiments, the water is in liquid form. In some embodiments, the water is in gaseous form. In some embodiments, the water is in a state of equilibrium between liquid and gas. In some embodiments, the water is in aerosol form. The water may contain other components (e.g., the water may be part of an aqueous solution). In some embodiments, the hydrothermal treatment step is carried out at a temperature of about 150°C to about 250°C, for example, about 180°C to about 220°C, about 190°C to about 210°C, about 200°C to about 210°C, or about 205°C. In some embodiments, the hydrothermal treatment step is carried out under increased pressure. In some embodiments, the increased pressure is between about 5 bar and about 30 bar. In some embodiments, the hydrothermal treatment step is carried out at autogenous pressure (typically 10 to 28 bar). In some embodiments, the hydrothermal treatment step is carried out in an autoclave. In some embodiments, the weight ratio of melamine in water (% w / w) is from about 1% to about 90%, such as from about 2% to about 50%, from about 5% to about 30%, or about 10%. When the weight ratio of melamine to water is lower, a greater amount of "rod-like" material tends to be formed. Without wishing to be bound by theory, it is believed that the more "rod-like" material that enters the calcining step, the more porous carbon nitride tubes are produced in the calcining step. The amount of "rod-like" material produced in the hydrothermal step and the size / size of the "rods" may also be affected by other parameters, such as temperature, melamine: water ratio, reaction vessel filling rate, and surface area of the reaction mixture. There is generally a correlation between the size of the porous carbon nitride tubes and the size of the "rods" of the "rod-like" material from which they are derived. In some embodiments, the length and / or diameter of the hole-containing carbon nitride tubes are the same or approximately the same as the length and / or diameter, respectively, of the "rod" of "rod-like" material from which they are derived.
[0048] In some embodiments, melamine and water are mixed before heat treatment so that melamine is dispersed in water. For example, melamine and water can be ultrasonically treated and / or mixed by stirring to obtain a dispersion. In a specific embodiment, melamine is uniformly dispersed in water.
[0049] During the hydrothermal treatment step, the orientation of the container containing melamine and water can be controlled to increase the surface area of the reaction mixture (comprising melamine and water). Thus, in some embodiments, the surface area of melamine and / or water is increased by orienting the reaction container in a particular orientation, for example, by laying a tall container on its side. In some embodiments, the increased surface area during the hydrothermal treatment results in the formation of higher rod-shaped hydrothermally treated melamine.
[0050] In the process of the present invention, melamine is hydrothermally treated in a reaction vessel (e.g. an autoclave) which is usually sealed and usually under pressure. In the context of the hydrothermal treatment step, the "filling rate" is the ratio of the volume occupied by melamine and water (and any other non-gaseous reagents that may be present) relative to the internal volume of the container. Taking the calculation of the "filling rate" as an example, if the internal volume of the container is 100 cm 3 , melamine occupies 10cm 3 , water occupies 40cm 3 , then the filling rate is 50%. As another example, if the internal volume of the container is 100cm 3 , melamine occupies 10cm 3 , water occupies 40cm 3 , and the solid reagent occupies 10cm 3 , then the filling ratio will be 60%. Lower filling ratios tend to produce a larger proportion of rod-like material, while higher filling ratios tend to produce a larger proportion of bulk material.
[0051] As used herein, "calcination" (and variants thereof, such as "calcination" and "calcined") refers to a heat treatment process carried out in the absence of oxygen or in a limited supply of oxygen to cause thermal decomposition or reaction. The absence of oxygen can be achieved by calcining under an inert atmosphere, such as under an argon or nitrogen atmosphere. Thus, in some embodiments, the hydrothermally treated melamine is calcined under an inert atmosphere such as argon or nitrogen. In other words, in some embodiments, the hydrothermally treated melamine is calcined in a sealed container, wherein the atmosphere within the sealed container is an inert atmosphere, such as argon or nitrogen. The limited supply of oxygen can be achieved by calcining in an atmosphere with limited air or oxygen, such as in a sealed container containing an air atmosphere, wherein the amount of oxygen can be exhausted during the process. Thus, in some embodiments, the hydrothermally treated melamine is calcined in a sealed container, wherein the atmosphere within the sealed container (at the beginning of the calcining step) is or comprises air. In some embodiments, the gases generated by the calcination of the hydrothermally treated melamine (e.g., gases generated by the thermal decomposition of the hydrothermally treated melamine) can form a major part of the atmosphere within the sealed container. In some embodiments, the gases generated from the initial stages of the calcination of the hydrothermally treated melamine serve as a protective gas for the remainder of the calcination step.
[0052] In the method of the present invention, the calcining step (step (b)) is carried out at a temperature of about 500°C to about 600°C. In some embodiments, the calcining step (step (b)) is carried out at a temperature of about 520°C to about 590°C, such as about 530°C to about 580°C, about 540°C to about 570°C, about 550°C to about 570°C, about 555°C to about 565°C, or about 560°C. Temperatures below about 500°C generally produce poorer results (e.g., lower surface area), which may be due to incomplete calcination. Temperatures above about 600°C generally produce poorer results (e.g., lower surface area), which may be due to decomposition. In some embodiments, the heating rate is about 1°C / min to about 50°C / min, such as about 2°C / min to about 20°C / min, about 3°C / min to about 15°C / min, about 5°C / min to about 10°C / min, about 5°C / min, or about 10°C / min. If the heating rate is too low (e.g., less than about 1°C / min), the time required to reach the desired temperature may result in prolonged exposure of the hydrothermally treated melamine to high temperatures, resulting in "burning" of the material. High heating rates (e.g., greater than about 50°C / min) may result in uneven heating, resulting in some material being "burned" while the remaining material is not fully calcined. This can be offset by keeping the material at a set calcination temperature for a period of time to allow the temperature in the reaction mixture to reach equilibrium. Therefore, in some embodiments, faster heating rates (e.g., 5°C / min or 10°C / min) may be preferred. As will be appreciated by those skilled in the art, the optimal heating rate may depend on other factors, such as the scale or specific heat capacity of the components (e.g., hydrothermally treated melamine, container, filler, etc.). In some embodiments, the calcination step is carried out in a sealed container in a tube furnace. In some embodiments, the calcination step is carried out in a sealed container in a muffle furnace. In some embodiments, the calcination step is carried out in a sealed container in a high temperature oven or the like.
[0053] As used herein, "sealed container" refers to a container that is sealed to prevent the entry or escape of gases or at least to prevent the entry or escape of gases in large quantities. It has been observed that sealed containers increase the yield of porous carbon nitride tubes, which is probably due to less material being "burned" or sublimated during the calcination step. In addition, the sealed container increases the surface area of the porous carbon nitride tubes obtained, thereby providing better hydrogen storage performance. The "sealed container" can be formed by various configurations of components (such as a container and a lid). For example, the container can be sealed by sealing the lid to the container (such as a crucible) with a sealant or glue or other similar substances. As will be understood, the sealant or glue should be able to withstand temperatures exceeding 500°C for the duration of the calcination process (or at least a considerable duration). There are many high-temperature sealants that may be suitable on the market, such as inorganic substances or ceramics, such as oxides (Al2O3, SiO2, Na2O, MgO, ZrO2), nitrides, borides and carbides. Other examples of high-temperature sealants that can be used for sealed containers include aluminum dihydrogen phosphate. The container can be formed of any suitable material. Suitably, the material should be able to withstand the high temperature of calcination, should be non-porous to gas and hydrothermally treated melamine and should be able to be sealed. Such materials include ceramics, steel, metals (e.g., Al, Pt, W, Ti, Rh, Au, Ag, Zr) and alloys with high melting points (e.g., above 600°C) and carbon-based materials such as graphite. In some embodiments, the sealed container is formed by ceramics. In some embodiments, a crucible (or other container of similar shape) is inverted and placed on a reaction vessel. The crucible can then be sealed on the bottom plate where the reaction vessel is located, thereby forming a sealed container that closes the reaction vessel. The sealed container can also be physically / mechanically sealed, for example, a threaded cap that is "screwed" into the threaded neck of the container so that it seals the neck of the container to form a sealed container. Other configurations include a cap that is held on the opening of the container by an external device (e.g., bolted connection). Various forms of sealed containers can be envisioned by those skilled in the art.
[0054] In the process of the present invention, the hydrothermally treated melamine is calcined in a sealed container. In the context of the calcination step, the "filling rate" is the ratio of the volume occupied by the hydrothermally treated melamine (and optional filler, as described below) relative to the internal volume of the sealed container. Taking the calculation of the "filling rate" as an example, if the internal volume of the sealed container is 100 cm 3 And the hydrothermally treated melamine occupies 50cm 3 , then the filling rate is 50%. As another example, if the internal volume of the sealed container is 100cm 3 , the hydrothermally treated melamine occupies 50cm 3 And the filler occupies 25cm 3, then the filling rate will be 75%. In another example, if the calcination step is carried out in a reaction vessel located in a sealed container, and the internal volume of the sealed container is 100cm 3 , the hydrothermally treated melamine occupies 50cm 3 , filler occupies 25cm 3 , and the reaction vessel (entirely located within the sealed container) occupies 10 cm 3 , then the filling rate will be 85%. Lower filling rates tend to produce lower yields, which may be due to more material being "burned off" or sublimated during the calcination step. Without wishing to be bound by theory, it is believed that when the material is "burned off" or sublimated, the gaseous material produced by the "burnout" or sublimation may form a protective gas on the remaining material used for the calcination process, so a larger filling rate may result in less material being consumed to form a protective gas, and thus a higher yield of porous carbon nitride tubes. In some embodiments, the filling rate is greater than about 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%. In some embodiments, the filling rate is as high as about 99%, 95%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20% or 10%. In some embodiments, the fill rate is from about 10% to about 99%, from about 20% to about 95%, from about 30% to about 90%, from about 40% to about 80%, or from about 50% to about 70%.
[0055] In some embodiments, the calcining step (step (b)) is carried out for at least a portion of the calcining step, typically the entire calcining step, with a filler in contact with the hydrothermally treated melamine. As used herein, "filler" refers to an inert particulate material that does not react during the calcining process but can be included therein to increase the filling rate in the sealed container. It is believed that the filler can perform more than one function. For example, the filler can also increase the surface area of the hydrothermally treated melamine. Without wishing to be bound by theory, it is believed that the increase in surface area achieved by adding fillers can provide more space for gas diffusion and enhance pyrolysis, thereby increasing the surface area of the CN tube. This effect may be more significant in a large container containing a relatively small amount of material, such as calcining a small amount of material in an apparatus having a relatively large size container. Examples of fillers include ceramic particles, such as Al2O3 particles, particles composed of or containing steel, metals (e.g., Al, Pt, W, Ti, Rh, Au, Ag, Zr) and alloys with high melting points (e.g., above 600°C), particles composed of or containing carbon-based materials such as graphite. In some embodiments, the inert particulate material is in the form of a ball. In some embodiments, the diameter of the ball is from about 1 mm to about 50 mm, for example, from about 5 mm to about 20 mm, from about 5 mm to about 15 mm or about 10 mm. As will be appreciated, the optimal size may depend on factors such as the amount of material to be calcined and the size of the reaction vessel. Those skilled in the art will be able to determine the appropriate amount and size of the filler. In some embodiments, the filler is or comprises Al2O3 balls. As will be appreciated, the addition of the filler increases the "filling rate", which may affect the performance of the porous carbon nitride tube produced by the method. In some embodiments, a filler (e.g., alumina balls) is added to achieve a predetermined filling rate, resulting in a porous carbon nitride tube having a lower density and / or a higher surface area than the porous carbon nitride tube produced by a similar process, wherein the same predetermined filling rate can be achieved by simply adding more hydrothermally treated melamine. In other words, in some embodiments, the addition of a filler can provide a porous carbon nitride tube having a lower density and a higher surface area. It is believed that the addition of a filler can further the reaction (from hydrothermally treated melamine to porous carbon nitride tube) toward completion.
[0056] Also provided herein is a porous carbon nitride tube obtained by the method of the present invention.
[0057] The porous carbon nitride tubes obtained by the method of the present invention can be used for absorbing, adsorbing and / or desorbing hydrogen and / or other gases (such as CO2, CH4, N2O, SO2, O3, H2O, fluorinated gases, biofuel gases, synthesis gas or mixtures thereof), especially hydrogen. Therefore, on the other hand, the present invention provides the use of the porous carbon nitride tubes obtained by the method of the present invention in absorbing, adsorbing or desorbing hydrogen and / or other gases (such as CO2, CH4, N2O, SO2, O3, H2O, fluorinated gases, biofuel gases, synthesis gas or mixtures thereof), especially hydrogen. As will be understood, the porous carbon nitride tubes obtained by the method of the present invention can therefore be used to absorb, store and / or transport hydrogen. Therefore, the present invention also provides a solid hydrogen storage material comprising the porous carbon nitride tubes obtained by the method of the present invention. In some embodiments, the solid hydrogen storage material is or comprises porous carbon nitride tubes in powder form. In some embodiments, the solid hydrogen storage material is or comprises porous carbon nitride tubes dispersed (e.g., embedded) in a matrix. In some embodiments, the matrix is a flexible matrix. In some embodiments, the matrix is a porous polymer. In some embodiments, the solid-state hydrogen storage material is or comprises a porous carbon nitride tube in solid form. In some embodiments, the solid-state hydrogen storage material is or comprises a porous carbon nitride tube in solid form obtained by compressing the porous carbon nitride tube in powder form. In some embodiments, the solid-state hydrogen storage material is or comprises a porous carbon nitride tube in porous sponge form. In some embodiments, the solid-state hydrogen storage material is reusable. In some embodiments, the solid-state hydrogen storage material is suitable for use as a transportable solid-state hydrogen storage material.
[0058] Examples
[0059] The present invention is now further described by reference to the following non-limiting examples.
[0060] Preparation of porous carbon nitride tubes using melamine
[0061] The porous carbon nitride tubes are prepared using a two-step process. The first step comprises hydrothermal treatment of melamine in a closed autoclave. The second step comprises calcination of the hydrothermally treated melamine. The carbon nitride material prepared by this process may be represented herein using the notation Hx-Cy-CN, where x = the temperature at which the hydrothermal treatment is performed, and y = the temperature at which the calcination is performed.
[0062] Preparation of porous carbon nitride tubes - hydrothermal treatment study
[0063] In a typical procedure, 5 g of melamine is loaded into a polyphenylene (PPL) container (50 mL tank capacity). Then 50 mL of deionized water is added to the container. The solution is ultrasonically treated for 15 minutes and stirred for 30 minutes to evenly disperse the melamine powder. After dispersion, the polyphenylene container containing the homogeneous solution is transferred to a stainless steel autoclave, and the polyphenylene container is sealed by the mechanical force provided by the stainless steel autoclave. The autoclave is heated at 200 ° C for 24 hours and cooled naturally. During the hydrothermal treatment, the melamine sample condenses under autogenous pressure. The white product is collected by filtration and washed five times with deionized water. The obtained product is then dried at 40 ° C for 12 hours.
[0064] A series of experiments investigating the conditions of the hydrothermal treatment step were conducted to examine the effect on the morphology of melamine and to improve the yield of porous carbon nitride tubes in the subsequent calcination step. In these experiments, a polyphenylene-lined autoclave with an internal volume of 70 mL was used. Melamine / deionized water solutions were prepared in different ratios and added to the polyphenylene-lined autoclave at different filling ratios. The samples were dispersed by ultrasonic treatment for 15 minutes and stirring for 30 minutes. The samples were then hydrothermally treated at different temperatures from 180°C to 220°C for 24 hours and cooled naturally. The hydrothermally treated melamine was filtered, washed and dried before calcination. The shapes of these melamine samples were observed by SEM, and the results showed that the concentrated samples had the best rod-shaped melamine cyanurate formation and the highest yield when the mass ratio of melamine / deionized water was 10%, the filling ratio was 85%, and the heating temperature was 205°C.
[0065] The morphology of melamine and hydrothermally treated melamine samples observed by SEM is shown in Figure 1 In. Pure melamine has an irregular structure ( Figure 1 a), and transformed into different configurations after hydrothermal treatment ( Figure 1 b-1r). The crystalline structure doped with dendritic melamine cyanurate was formed by a typical hydrothermal treatment, in which 5 g of pure melamine plus 50 mL of deionized water were heated at 200°C for 24 hours in a 50 mL autoclave ( Figure 1 b). The size of dendritic melamine cyanurate is generally larger than that of rod-shaped melamine cyanurate. Tubes produced from calcined dendritic melamine cyanurate may have a larger tube diameter, resulting in a lower surface area per unit weight of material.
[0066] A series of experiments to observe hydrothermal treatment were designed and performed to increase the amount of rod-like material, as shown in Table 1. Three main factors, including heating temperature (top row), weight ratio of melamine / deionized water (left column) and filling ratio (right column), were varied to observe the effect on the shape of the hydrothermally treated melamine samples. A polyphenylene-lined autoclave with a volume of 70 mL was used in this study.
[0067] To investigate the effects of these factors on the morphology of hydrothermally treated melamine, the microstructures of different samples were compared. From the samples synthesized at various heating temperatures with fixed solution concentrations and filling ratios, it can be seen that with increasing temperature, the formation of rod-shaped melamine cyanurate is enhanced, while the yield of the product is greatly reduced. This may be due to the increase in the solubility of melamine in water with increasing temperature, resulting in a higher alkaline solution concentration caused by the condensation of melamine to form ammonia. The alkaline environment promotes the hydrolysis of melamine and its conversion into cyanuric acid by replacing the amino group with a hydroxyl functional group. Melamine and cyanuric acid can be combined together through hydrogen bonds to form melamine cyanurate, which is a large molecule that is easily precipitated due to reduced solubility. The reduction in the amount of product may be related to the increase in the autogenous pressure during the hydrothermal process with increasing temperature, which may cause more severe container deformation and force the dissolved melamine cyanurate to escape through pressurized steam. This hypothesis can be supported by the observation of white solid residues on the inner wall of the stainless steel autoclave.
[0068] By comparing Figure 1 f and 1p, Figure 1 k and 1q, Figure 1 n and 1o, and Figure 1 m and 1r, it can be found that the lower the ratio of melamine to deionized water, the greater the amount of rod-like melamine cyanurate. It is believed that when less melamine reactant is used at a low solution concentration, a more complete hydrolysis and cross-linking reaction to form melamine cyanurate can be achieved.
[0069] The effect of “filling ratio” was explored by examining the sample morphology at 10% melamine / deionized water at 200°C. It was found that low filling ratios had better gain in rod-shaped melamine cyanurate. This is because less melamine is loaded at low filling ratios at a fixed solution concentration. Therefore, a more complete hydrothermal reaction is expected. Another reason may be that lower autogenous pressure is generated at low filling ratios, which leads to spontaneous reactions to produce more NH3 gas, thereby increasing the formation of cyanuric acid and the yield of melamine cyanurate.
[0070] A sample that was well converted to rod-shaped melamine cyanurate is shown in the enlarged image: Figure 1d1, 1f1, 1i1, 1l1 and 1m1. The lengths and diameters of the melamine cyanurate rods are listed in Table 2. The results show that when synthesized at higher temperatures and lower filling rates, the samples have reasonable sizes, with lengths of tens of μm and diameters of 1 to 3 μm. However, the yield of the product is relatively low. Considering that a larger sample amount is required for the calcination process and hydrogen storage measurements, the sample size used for preparation in this study was 2.5 μm. Figure 1 The parameters of the sample shown in l (sample 1l) were taken as the optimal method for hydrothermal treatment.
[0071] Table 1: Experimental parameters and yields of products in hydrothermal treatment
[0072]
[0073] Table 2: Size of rod-shaped melamine cyanurate under different synthesis conditions
[0074] Figure 1 d Figure 1 f Figure 1 i Figure 1 l Figure 1 m Rod length (μm) 45-149 21-48 18-69 50-154 41-80 Rod diameter (μm) 1.3-3.2 0.9-2.3 1.1-1.6 1.7-14.2 0.9-2.4
[0075] In order to evaluate the reproducibility in a larger container, a PPL-lined autoclave with a capacity of 100 mL was used in an additional experiment. The preparation parameters of sample 1 l were implemented to synthesize rod-shaped melamine cyanurate. However, a large number of lumps of melamine cyanurate with a size of tens of micrometers were found in the product, indicating a poor conversion effect, such as Figure 2 A solid cylinder made of polytetrafluoroethylene with a volume of 30 mL was then placed in the container to occupy the internal volume in order to simulate the same volume used when preparing sample 1l. Figure 2 As shown in b, the treated sample still contains a considerable amount of melamine cyanurate. Then the 100 mL autoclave was placed horizontally in the oven to increase the reaction surface of melamine and water. SEM image ( Figure 2 c) shows a high degree of conversion to rod-like material with a diameter of about 3 μm, indicating that the surface area of the reaction mixture is very important for the formation of rod-like samples. This correlation may be beneficial for scaling up the process.
[0076] The crystal structures of commercially available melamine and melamine cyanurate concentrated under different hydrothermal treatment conditions are reflected in the XRD patterns ( Figure 3 ). Figure 3 The samples denoted as (a) to (r) correspond to Tables 1 and Figure 1The sample shown in . The change in the peak distribution indicates that a new arrangement of the melamine structure has occurred after the hydrothermal reaction. Three peaks appear at around 10.9°, 18.4° and 21.96°, labeled as (100), (110) and (200), which are evidence of in-plane stacking in the melamine-cyanuric acid complex. In addition, an intense peak observed at around 28°, which can be labeled as (002), is indicative of lamellar stacking of melamine cyanurate. Due to the changes in the sample morphology under different synthesis conditions, the intensity of the peaks varies according to different growth directions and preferred orientations. For example, samples containing mainly block or flake melamine cyanurate have very high intensities in the (002) peak, such as Figure 3 (b), (c), (e), (g), (n), (o), (p) and (r) are shown. In contrast, the samples with high conversion of rod-shaped melamine cyanurate show a significant decrease in the (002) peak. Figure 3 The absence of the above peak in (q) indicates that the formation of melamine cyanurate is incomplete.
[0077] In addition to XRD, the formation of melamine cyanurate was further confirmed by FT-IR, such as Figure 4 The samples selected for FT-IR analysis were pure melamine, typical HT melamine (hydrothermally treated by a typical method) and optimized HT melamine (hydrothermally treated with optimized parameters: 1l in Table 1). -1 The appearance of two new peaks at 810 to 764 cm indicates the presence of C=O stretching vibration in melamine cyanurate. In addition, due to the hydrogen bonding between cyanuric acid and melamine, the vibration frequency of the triazine ring of melamine is reduced; from 810 to 764 cm -1 .
[0078] The hydrothermally treated samples in this study exhibited XRD and FT-IR spectra consistent with melamine cyanurate (referred to herein as hydrothermally treated melamine or melamine cyanurate).
[0079] Preparation and Calcination of Porous Carbon Nitride Tubes
[0080] In a typical process, the hydrothermally treated melamine was calcined in air at 560°C for 4 hours in a sealed crucible with alumina balls as filler. For comparison, another batch of this sample was loaded into a boat alumina crucible placed in a semi-closed quartz tube and calcined at 600°C for 4 hours under Ar atmosphere. These two porous carbon nitride tube materials are denoted as H 205 -C 560 -CN and H 205 -C 600In addition, for comparison, bulk graphitic carbon nitride (g-CN) was synthesized by calcining pure melamine powder at 600 °C for 4 h in a semi-closed quartz tube under an atmosphere of Ar gas.
[0081] Various parameters such as sample amount, sample grinding, crucible airtightness, furnace type, protective gas, filler, heating rate, heating duration and heating temperature were also evaluated to study the effect of calcination conditions on the properties of the final product. The conditions that produced the best yield and the highest surface area, as measured by specific surface area (Brunauer-Emmett-Teller, BET) analysis, were: 1.8 g of the prepared hydrothermally treated melamine was contained in a sealed crucible; alumina balls were used as fillers; and calcined at 560°C in air for 4 hours at a heating rate of 5°C / min. After calcination, a light yellow substance was collected and determined to be CN by XRD. The sample prepared according to these conditions, denoted as H 200 -C 560 -CN (Hx-Cy-CN: x: hydrothermal temperature; y: calcination temperature), was selected as one of the candidates for hydrogen storage test.
[0082] The calcination parameters and results for preparing carbon nitride materials are shown in Tables 3 and 4. Pure CN was synthesized by charging pure melamine powder into an Al2O3 boat crucible placed in the middle of a quartz tube and heating at 600°C for 4 hours under Ar. In order to investigate the optimal calcination conditions for porous carbon nitride tubes, a melamine cyanurate sample ( Figure 1 b) It was observed that several factors influence the calcination results. For example, if the amount of hydrothermally treated melamine is low, the yield is usually very low, probably due to severe sublimation.
[0083] The limited chamber size of a tube furnace makes it less suitable for large-scale production. Therefore, a method was developed to increase the product yield using a muffle furnace. Advantageously, the method can be extended to other heating devices. In this particular method, a cup-shaped crucible containing melamine is placed on an Al2O3 plate and covered with a larger inverted cup-shaped crucible. The gap between the plate and the edge of the larger crucible is sealed with a high-temperature sealant, aluminum dihydrogen phosphate. In this case, the sublimation of carbon nitride is significantly reduced, probably due to the pressure generated by the condensation process.
[0084] It was observed that the temperature of the calcination process below 600°C was more favorable for the synthesis of porous carbon nitride tubes. Higher temperatures and longer heating times lead to a significant reduction in product yield. However, low temperatures may lead to incomplete pyrolysis. For example, the surface area of the porous carbon nitride tubes obtained at 500°C is lower than that obtained at 560°C, which is discussed later under the heading "Surface Area Analysis". On the other hand, the effect of the heating rate on the results may not be very significant.
[0085] Al2O3 balls as fillers can provide more space for gas diffusion and promote pyrolysis, thereby increasing the surface area of porous carbon nitride tubes. This is further described in the BET surface area section below. Grinding of hydrothermally treated melamine samples seems to destroy the tubular structure of porous carbon nitride tubes. Therefore, grinding of rod-shaped melamine cyanurate should be avoided. The best results were obtained using a larger amount of as-prepared hydrothermally treated melamine in a sealed crucible at 560°C for 4 hours in air with alumina balls as fillers.
[0086] Table 3: Calcination conditions of pure melamine and prepared melamine cyanurate
[0087]
[0088] Table 4: Calcination conditions of ground melamine cyanurate
[0089]
[0090] a Two different types of melamine samples. "Pure" is the original melamine, and "HT" is the hydrothermally treated melamine (i.e. Figure 1 sample shown in b).
[0091] b "Yes" indicates that the melamine samples were ground in a mortar before calcination, and "No" indicates the prepared samples.
[0092] c The weight of the hydrothermally treated melamine sample loaded for calcination.
[0093] d Two different types of alumina crucibles, cups and boats.
[0094] e "Semi-closed" refers to a cup-shaped crucible covered by an alumina lid or a quartz tube, where the boat crucible is loaded at the open end and filled with insulation. "Yes" means that the cup-shaped crucible is placed on an alumina plate and covered with a larger cup-shaped crucible, and then the gap between the lid and the larger crucible is sealed with aluminum dihydrogen phosphate, which is a high-temperature sealant.
[0095] f The hydrothermally treated melamine samples were either loaded directly into the crucible or separated by alumina balls (ie fillers).
[0096] g Two different types of furnaces are used for calcination: muffle furnaces for cup-shaped crucibles and tube furnaces for quartz tubes containing boat crucibles.
[0097] h The hydrothermally treated melamine samples were calcined in air or in a protective gas such as Ar and N2.
[0098] i Calcination heating rate.
[0099] j The heating duration of calcination.
[0100] k The heating temperature used for calcination.
[0101] l The weight of the carbon nitride sample obtained after calcination.
[0102] m The weight percent of carbon nitride sample remaining after calcination.
[0103] Morphological studies
[0104] In order to study the effect of calcination conditions on the morphology of porous carbon nitride tubes, some selected samples (prepared in various pyrolysis states (Table 5)) were observed by SEM, as shown in Figure 5 The heating rate for calcination is not shown in the table because it was fixed at 5°C / min.
[0105] Table 5 and Figure 5 The following observations were made. First, the pyrolysis using a boat crucible and a tube furnace was able to convert the produced rod-shaped melamine cyanurate into tubular carbon nitride ( Figure 5 g to 5j). When the heating cycle is doubled, carbon nitride tubes can still be formed ( Figure 5 h). In contrast to the tube furnace, the muffle furnace connected to the semi-enclosed cup-shaped crucible burns the CN tube, leaving only flake CN ( Figure 5 a). However, if the cup-shaped crucible is sealed, the muffle furnace ( Figure 5 b to 5f) can achieve tube formation similar to that given by a tube furnace. The advantages of this method over using a tube furnace are that muffle furnaces are generally more common and cheaper than tube furnaces, and the method can be used to produce larger quantities of porous carbon nitride tubes. From the SEM images ( Figure 5 b and 5d) it is difficult to discern the effect of filler on morphology, but differences are shown in surface area (discussed under the heading “Surface area analysis”). Note that the rod-like structure of melamine cyanurate is destroyed by grinding and only some porous framework remains after calcination ( Figure 5 k).
[0106] Table 5: Pyrolysis conditions for preparing CN tubes
[0107]
[0108] Four carbon nitride samples were selected for further characterization and hydrogen storage measurement, namely: (a) bulk g-CN: pure carbon nitride was synthesized by calcining pure melamine powder at 600 °C for 4 h in a semi-closed quartz tube under Ar gas protection; (b) H 200 -C 560 -CN: Typical HT (hydrothermally treated) melamine was charged into a sealed crucible with alumina balls as filler and calcined in air at 560 °C for 4 h at a heating rate of 5 °C / min; (c) H 205 -C 560 -CN: Optimal HT melamine was calcined in a sealed crucible with alumina balls as fillers at 560 °C in air for 4 h; (d) H 205 -C 600 -CN: Best HT melamine was loaded in a boat crucible placed in a semi-closed quartz tube and calcined at 600°C for 4 hours under Ar atmosphere. Figure 6 SEM images of the four samples are shown.
[0109] Bulk g-CN shows an irregular structure, which is completely different from the other three samples. 200 -C 560 -CN has a tubular structure and a cotton-like skeleton because of its relatively low content of rod-like materials before calcination. The cotton-like skeleton can be converted from bulk melamine cyanurate in the original sample. 205 -C 560 -CN and H 205 -C 600 Both H-CN are prepared from HT melamine with a high proportion of rod-like structure. However, the morphology of the carbon nitride products is different using different calcination methods. 205 -C 560 -CN has a higher CN tube length ratio in the range of tens of microns, while H 205 -C 600 -CN showed shorter CN tube length. This suggests that even if calcined under argon atmosphere, too high calcination temperature may have an adverse effect on H 205 -C 600 -The tubular structure of the CN sample caused some damage.
[0110] Characterization and performance
[0111] Characterization
[0112] The morphology was observed using a Hitachi 3400X scanning electron microscope (SEM) equipped with a secondary electron (SE) detector at an operating voltage of 20 kV, and the element distribution was determined by an energy dispersive X-ray spectrometer (EDS) at 15 kV. The detailed morphology was characterized by a transmission electron microscope (TEM, Phillips CM200). The TEM samples were prepared by dispersing the powder in ethanol and collecting the dispersed samples by a copper grid. The samples were then dried at 40 °C for one day before TEM characterization. The TEM images were taken using a 40 °C laser with Cu Kα radiation. The PANalytical Xpert Pro MPD X-ray diffractometer was used to study the crystal structure and phase identification at an operating voltage of 45kV and a current of 40mA. The analysis of the diffraction pattern was completed using X'pert HighScore Plus software. After degassing at 150°C for 3 hours to remove moisture, the surface area and internal pore characteristics were measured at 77K using a Micromeritics TriStar3000 analyzer using a specific surface area (BET) method and pore size distribution (Barrett-Joyner-Halenda, BJH) desorption method. Fourier transform infrared spectrometer (Spectrum 100, PerkinElmer) was used to study the pore size distribution in the UATR mode from 600 to 4000cm -1 Scanning of functional group vibrations.
[0113] Composition analysis
[0114] Energy dispersive X-ray spectroscopy (EDS) was used to analyze the composition of carbon nitride materials. Figure 8 Three major elements were shown: carbon, nitrogen and oxygen in all samples, and the quantitative results are shown in Table 6. The results show that the nitrogen content is high in the samples; the nitrogen content is between 41 at% and 55 at%.
[0115] Table 6: Composition distribution of selected CN materials
[0116]
[0117]
[0118] Surface area analysis
[0119] The pore structure of the selected carbon nitride materials was investigated by nitrogen adsorption measured at 77 K. The pore properties such as surface area, pore volume and average pore size are shown in Table 7, and the nitrogen adsorption-desorption isotherms are shown in Fig. 9In addition to the four selected samples evaluated for hydrogen storage, two additional samples were examined by BET surface area analysis to investigate the effect of fillers on the pore structure and the effect of calcination temperature on the pore structure. The two samples were: (1) “H 200 -C 560 -CN" ( Figure 5 b) Its use is similar to H 200 -C 560 -CN was prepared in a similar manner, but without filler loaded in the crucible, and (2) "H 200 -C 500 -CN" ( Figure 5 c), which is used to prepare H 200 -C 560 The same HT melamine of -CN was calcined at 500°C instead.
[0120] Based on the IUPAC classification, all N2 adsorption-desorption isotherms can be classified as type IV isotherms and type H3 hysteresis loops, indicating the presence of mesopores and capillary condensation in the pores. As can be seen in Table 7, in the selected samples, H 205 -C 560 -CN has the highest surface area, 148.69m 2 / g, which is larger than the surface area of bulk g-CN (21.38m 2 / g) is about 7 times higher. The high specific surface area may be attributed to the high proportion of tubular CN and its porous structure. Interestingly, although 205 -C 560 -CN synthesis uses the same HT melamine, but H 205 -C 600 -CN has a relatively low surface area (51.54 m 2 / g) and a larger average pore size (34.85nm). This may indicate that higher calcination temperatures (e.g. >600℃) may lead to the loss of CN tubes, which may be due to the large surface area of the tubes being easy to sublimate, which is consistent with Figure 6 The SEM image shown in d is consistent.
[0121] H 200 -C 560 -CN has a reasonable surface area (105.98m 2 / g) and a smaller pore size (5.88nm). However, if no filler (e.g., Al2O3 balls) was placed in the crucible during calcination, the surface area dropped significantly by 24% to 80.33m 2 / g(H without filler 200 -C 560 -CN). If the pyrolysis temperature is reduced to 500°C, the surface area decreases significantly by 49% to 54.27 m2 / g(H 200 -C 500 -CN), and the pore volume (0.098 cm 3 / g) is even lower than the pore volume of bulk g-CN (0.176 cm 3 / g), indicating that its ability to transform into a porous structure is poor.
[0122] The pore size distribution of the selected CN materials is as follows Fig.10 It can be observed that the two samples, bulk g-CN and H 205 -C 600 -CN were all calcined at 600 °C under Ar, with a wide pore size region greater than 30 nm, which may be due to the deficiency of tubular CN. In contrast, the other samples calcined at 560 °C in an isolated environment (i.e., a sealed container) had a narrow pore size range centered around 4 nm.
[0123] In general, calcination temperatures above about 600°C or below about 500°C tend to reduce the surface area of the resulting porous carbon nitride tubes, which may be due to the fact that calcination temperatures above about 600°C (even in Ar (g) The results showed that the decomposition of CN tubes in a molten-carbon atmosphere (under a molten-carbon atmosphere) was increased or incomplete calcination below about 500° C. It was observed that a moderate temperature of about 560° C. was suitable for preparing porous carbon nitride tubes with high surface area. In addition, it was observed that calcination in a sealed container (e.g., a sealed crucible in a muffle furnace) was an advantageous way to produce a large amount of high-quality CN samples.
[0124] Table 7: BET surface area characteristics of carbon nitride materials
[0125] sample <![CDATA[Surface area (m 2 / g)]]> <![CDATA[Pore volume a (cm 3 / g)]]> <![CDATA[Aperture b (nm)]]> Bulk g-CN 21.38 0.176 21.08 <![CDATA[H 200 -C 560 -CN]]> 105.98 0.183 5.88 <![CDATA[H without filler 200 -C 560 -CN c > 80.33 0.139 6.21 <![CDATA[H 200 -C 500 -CN d ]]> 54.27 0.098 5.74 <![CDATA[H 205 -C 560 -CN]]> 148.69 0.232 5.57 <![CDATA[H 205 -C 600 -CN]]> 51.54 0.408 34.85
[0126] a BJH desorption cumulative pore volume.
[0127] b BJH desorption average pore size.
[0128] c By synthesizing H 200 -C 560 -CN method, but no filler was present during the pyrolysis process ( Figure 5 b).
[0129] d By synthesizing H 200 -C 560 -CN method, but the calcination temperature was 500℃( Figure 5 c).
[0130] *The samples in the thick frame are for comparison of the pore characteristics of CN materials prepared under three different pyrolysis conditions.
[0131] XRD studies
[0132] The crystal structure of the selected carbon nitride materials was studied by XRD, such as Fig.11 As shown. All treated samples have two main diffraction peaks, which are in good agreement with bulk g-CN. This shows that after undergoing different heat shrinkage treatments, the crystal structure of the hole-containing carbon nitride tubes remains unchanged from that of bulk g-CN. The peak at 12.76° corresponds to the layer of the tri-s-triazine unit, which has been indexed as the (210) plane in orthorhombic geometry. The strong peak at 27.7°, identified as the (002) plane, reflects the inter-plane distance between the stacked graphene layers of the conjugated aromatic system. As Fig.11 The samples containing tubular CN ( Fig.11 The low-angle (210) peak intensity of the samples (b to 11d) is less significant than that given by bulk g-CN. This may be due to the reduced planar size of the porous carbon nitride tubes. In addition, the weaker high-angle (002) peak intensity provided by the tubular samples may be attributed to the smaller size and looser stacking of the graphitic CN layers.
[0133] FTIR studies
[0134] The structures of the functional groups in the four selected carbon nitride materials were further investigated by FTIR spectroscopy, e.g. Fig.12 The IR spectra of the four samples are almost the same, indicating that the chemical structure of the porous carbon nitride tubes is similar to that of bulk g-CN. That is, the hydrothermal treatment only changes the physical structure of g-CN, not the chemical structure. 806cm -1 The bands at 1230, 1313 and 1396 cm represent the breathing mode of the tri-s-triazine ring unit. -1 The peaks at 1568 and 1627 cm correspond to the aromatic CN stretching. -1 The peaks near 3000 to 3500 cm -1 The broad absorption band in the region may be related to the NH stretching and OH bonding of adsorbed water molecules.
[0135] Hydrogen storage performance
[0136] Hydrogen storage and kinetic measurements were performed using a volumetric method with a Sievert instrument, utilizing ultra-high purity hydrogen (99.999%) to avoid unwanted toxic gases. The dead volume of the system chamber was calibrated by introducing hydrogen at 0.1 to 0.5 MPa at different temperatures according to Japanese Industrial Standard H 7201 (JIS H 7201). Prior to the hydrogen storage studies, the carbon nitride samples were placed in a vacuum (10 -3The mixture was degassed at 150° C. for 4 h at 400° C. (torr) to eliminate moisture and residual gas, and then cooled to room temperature.
[0137] The activated samples were gradually added with pure hydrogen at room temperature, and then the equilibrium values at different pressures were recorded. The desorption study was established by isothermally reducing the hydrogen pressure in the system chamber. These operations were repeated to measure the hydrogen storage capacity of all samples at 50°C and 100°C, respectively. Before each measurement, the samples were evacuated under vacuum at 150°C for 4 hours. Based on the calculation of the pressure drop, the hydrogen storage capacity can be obtained as a weight percentage and plotted in the form of a pressure-composition-isotherm (PCI).
[0138] Since the samples were found to have a low hydrogen uptake rate and a very high desorption rate at or above 50°C, the hydrogen uptake / desorption kinetics of the samples were studied only at room temperature. The uptake rate was measured under sudden exposure to 3.6 MPa pure hydrogen; the desorption rate was measured under vacuum at the same time. The pressure drop as a function of time was recorded.
[0139] The chemisorption of hydrogen was also measured by Chemisorption 2750 (Microbiology) from room temperature to 500°C. Before the chemisorption studies, the Ar (g) The sample was filled with 10% v / v H 2(g) .
[0140] like Fig.13 As shown in Figure 2, the hydrogen storage capacities of four selected CN materials were investigated volumetrically at room temperature and H2 pressures up to 3.6 MPa. 200 -C 560 -CN、H 205 -C 560 -CN and H 205 -C 600 The maximum hydrogen absorption capacity of -CN is 0.19wt%, 0.31wt%, 0.62wt% and 0.28wt% respectively. 205 -C 560 -CN provides the largest hydrogen capacity of 0.62 wt%, which may be due to its largest surface area. Fig.14 As observed in Figure 2, the hydrogen storage capacity of the CN samples shows good agreement with the changes in surface area. Since the results of EDS, XRD, and FTIR do not show obvious differences in the elemental distribution, crystal structure, and chemical structure of the samples, the differences in BET surface area may be the key determinant of the hydrogen storage properties of these CN materials.
[0141] Except for the measurements at 20°C, H 205 -C 560 The hydrogen storage capacity of -CN was further characterized at 50 °C and 100 °C, as Fig.15 As shown in H 205 -C 560 The absorption / desorption capacity of CN is quite limited at 50 °C and 100 °C, indicating that it is difficult to physically adsorb hydrogen molecules and chemisorb hydrogen atoms on the CN surface to form chemical bonds at higher temperatures. In addition, most of the hydrogen absorbed at 20 °C is able to be released at room temperature, which shows a favorable storage reversibility. This is further supported by the chemical adsorption test ( Fig.16 ), wherein firstly H 205 -C 560 -CN was filled with 10% H2+Ar and then dynamically discharged by heating from room temperature to 500°C. The sample charged at 20°C showed a significant desorption peak at about 25°C and a lower peak at 60°C, indicating that the main desorption occurred at room temperature, while the complete desorption occurred at 60°C. The samples charged at 50°C and 100°C both showed desorption peaks at about 40°C, which is lower than their absorption temperature. This desorption may originate from the residual hydrogen adsorbed on the surface of the material, and hydrogen is relatively easy to escape from the surface at close to room temperature. The results of chemical adsorption are consistent with Fig.15 The results of hydrogen storage capacity measured by volume method are consistent with those of 205 -C 560 -CN is a room temperature operating material.
[0142] H 205 -C 560 The absorption and desorption kinetics of -CN were investigated by suddenly exposing the samples to pure hydrogen at 3.6 MPa and vacuum conditions, respectively. Fig.17 As shown, H 205 -C 560 -CN was able to completely absorb and desorb hydrogen within 1 and 2.5 min, respectively, implying fast kinetics. This could be attributed to the porous structure of the CN tube, where the reaction sites were either saturated with H2 or vacated quickly because hydrogen molecules could easily diffuse through the CN tube wall.
[0143] Based on the absorption capacity characterized at 20 °C, it is inferred that H 205 -C 560 -CN has a H2 capacity of up to 10MPa, such as Fig.18 As shown in , it shows that the tubular carbon nitride material is expected to absorb 2.62 wt% hydrogen at 10 MPa. As will be appreciated by those skilled in the art, due to its highly porous structure, the porous carbon nitride tubes are also useful for the absorption, adsorption and / or desorption of gases other than hydrogen.
[0144] It should be understood that, if any prior art publication is referred to herein, such reference does not constitute an admission that the publication forms part of the common general knowledge in the art, in Australia or any other country.
[0145] In the subsequent claims and foregoing description of the present invention, unless the context requires otherwise due to explicit language or necessary implication, the use of the word "comprise" or variations such as "comprises" or "comprising" is inclusive, that is, specifying the presence of stated features but not excluding the presence or addition of other features in various embodiments of the present invention.
Claims
1. A method for preparing a porous carbon nitride tube, the method comprising: (a) hydrothermally treating melamine by subjecting the melamine in contact with water to a temperature of from 100° C. to 300° C.; and (b) calcining the hydrothermally treated melamine at a temperature of 500° C. to 600° C. in a sealed container, wherein the hydrothermally treated melamine is in contact with a filler during the calcination step (b), wherein the filler is inert under the calcination conditions, and wherein the filler is in the form of ceramic particles, or in the form of metal particles or alloy particles having a melting point above 600° C., or in the form of carbon-based particles.
2. The method according to claim 1, wherein the temperature in step (a) is 180°C to 220°C.
3. The method according to claim 1, wherein the temperature in step (b) is 540°C to 580°C. The method of claim 1 , wherein the pores have a diameter of 1 nm to 15 nm. The method of claim 4 , wherein the pores have a diameter of 3 nm to 7 nm. The method of claim 1 , wherein the tube has a diameter of 0.2 μm to 20 μm. The method according to claim 1 , wherein the tube has a length of 15 μm to 150 μm.
8. The method of claim 1, wherein the filler is in the form of ceramic Al2O3 particles.
9. A pore-containing carbon nitride tube obtained by the method according to any one of claims 1 to 8.
10. Use of a porous carbon nitride tube obtained by the method according to any one of claims 1 to 8 in the adsorption or desorption of hydrogen.
11. A solid hydrogen storage material comprising a porous carbon nitride tube obtained by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Transition metal filled carbon nanotube, preparation method and application thereof
CN109573983A
Hollow tubular g-C3N4 photocatalyst and preparation method and application thereof
CN109806901A